ICF in Bachelor degree programs-the implementation of the ICF in the clinical reasoning process of physical therapists for neurological patients-optimizing the health curriculum for comprehensive patient care - Hannes Aftenberger; Bernhard Taxer (Frontiers Media S.A., 2024)
The International Classification of Function, Disability, and Health (ICF) is known to be a valuable classification model in interprofessional neurorehabilitation, as it can lead to more patient-centered and self-determined treatment. To acquire the competencies implementing the ICF in the field of neurorehabilitation, it is important to anchor essential skills in the basic training of healthcare professionals. The Institute of Physiotherapy at FH JOANNEUM in Graz/Austria developed a concept to help students learn the necessary skills for implementing the ICF in a structured way. In the area of neurorehabilitation, we linked the ICF model with the Clinical Reasoning Model (CR). Competences are acquired over six semesters. Besides the general topics relating to the ICF (such as history, intention, and language) and CR that are taught in the first year, we focus in the later semesters explicitly on transferring these skills to neurorehabilitation. Therefore, we use interprofessional group work and problem-based courses as essential didactic elements for this transfer of skills. This article aims to show how the ICF could be implemented in Bachelor's degree programs for physiotherapy as well as in other healthcare programs. The authors' experiences are described and some best practice examples when working with the ICF in this field are given.